A systematic literature review on the application of problem-based learning in students' critical thinking abilities - Kusumo, Bangun Jati; Novaliyosi; Yuhana, Yuyu; Syamsuri (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
This study aims to explain and evaluate the application of the Problem-Based Learning (PBL) model to students' critical thinking skills based on established indicators, and to examine the distribution of publication years in relation to the educational levels of the research subjects. This systematic literature review employs a meta-analysis approach to obtain article findings that meet the predetermined inclusion criteria. The study follows a protocol based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The final set of primary studies selected for review consists of four research and development (R&D) studies and thirteen quasi-experimental studies. The results show that: (1) 47.06% of the studies applied the PBL model based on theoretical characteristics defined by experts; (2) 52.94% of the studies incorporated critical thinking indicators formulated by experts; (3) 52.94% of the primary studies related to PBL and critical thinking were published in 2020; and (4) the distribution of educational levels in the studies was as follows: elementary school (17.65%), junior high school (35.29%), senior high school (23.53%), and higher education (23.53%). This study offers novelty by integrating systematic literature review and meta-analysis approaches to evaluate the implementation of the PBL model in fostering critical thinking skills, based on expert-formulated indicators. By quantitatively identifying the proportion of articles aligned with PBL theory and critical thinking indicators, and by mapping publication trends by year and educational level, this study provides a comprehensive and current overview of PBL implementation practices in the context of Indonesian education.